Plurilateral trade agreements: An escape route for the WTO? - Rudolf Adlung; Hamid Mamdouh (World Trade Organization (WTO), 2017)
There are essentially two types of plurilateral trade agreements (PAs) among WTO Members, an exclusive and an open variant. While the benefits of the former agreements are shared among participants only, the latter are implemented on an MFN-basis, thus profiting non-signatories as well. The most prominent examples are the Information Technology Agreement (1996) and the Fourth and Fifth Protocols under the GATS (1997) on telecom and financial services, respectively. To preclude "free riding", their entry into force was made contingent on the participation of a "critical mass" of countries. The respective benchmarks, usually market shares of some 80% or more, are quite challenging, however. To promote more widespread use of plurilaterals, given the plethora of pressing policy concerns, whether investment-, competition- or labour-related, and the persistent stalemate in the Doha Round negotiations, the conclusion of exclusive agreements is thus being (re-)considered in ongoing policy discussions. This article takes a sceptical view, since any such PA would need to be agreed by consensus among all 160-odd WTO Members. It may prove more rewarding to further explore the potential of open agreements to address policy concerns among interested Members either in the form of co-ordinated improvements of their current schedules or, if not covered by existing treaty frameworks, as "WTO-extra" understandings.
Keywords: F13; F15; F53; 330; WTO; Doha Round; plurilateral agreements; critical mass